(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study examines the linguopoetic features of metaphors used in the literary work One Thousand and One Nights. The research analyzes the theoretical foundations of metaphor, its role in literary discourse, and its contribution to text formation. Metaphorical units found in the work are classified according to their semantic and functional characteristics, and their significance in portraying characters’ emotions, psychological states, and artistic images is revealed. The study also identifies the role of metaphors in ensuring textual coherence, enhancing aesthetic impact, and expressing the author’s artistic intention.